The Term Waswas and Obsessive-Compulsive Disorder (OCD) In Islamic Perspectives: English - Mohd Zahir Abdul Rahman,; Shah Rizul Izyan Zulkiply,; Ahmad Murshidi Mustapha, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
The term waswas appears five times in the Quran and seven times in seven Hadith books collections. Its interpretations by exegetes and scholars in Islamic studies vary, but one is associated with obsessive-compulsive disease (OCD). This is a study of the term waswas with the express objective of identifying its components that correspond to a contemporary understanding of OCD. This is a qualitative study that employs content and document analysis to examine chosen Islamic interpretation of the al-Quran, Hadith and traditional scholar viewpoints, with an emphasis on three characteristics of OCD: obsession, compulsive behaviour, and causation. The Quran and Hadith constitute the final miracle, transcending geographical and generational boundaries. Although OCD appears to be a recent diagnosis, its essence is mentioned in the magnificent Al-Quran. Keywords: Waswas, Obsessive-compulsive disorder (OCD), al-Quran, Hadith